Amthal al-Qur’an: Kajian Atas Keindahan Retoris al-Qur’an - Ridho, Muh. Makhrus Ali (Akademika, 2020)
al-Qur'an uses a variety of ways in conveying the messages of the teachings they contain, one of the methods used is by using the form amthal (parable).Amthal al-Qur'an is showing something that is in the mind (abstract) with a description of something that can be sensed (concrete), through a beautiful and enchanting disclosure, either by way of isti'arah, kinayah or prayer beads.The amthal al-Qur'an elements include; There must be something likened (al-musyabbah), that is something that will not be told, there must be origin of the story (al-musyabbahbih) that is something that is used as a place of equalization, there must be an aspect of equality (wajhulmusyabbah), namely the direction of equality between the two things that are delivered it.Kinds of amthal al-Qur'an are; amthal musarrahah,amthal kaminah and amthal mursalah.andsigignification of amthal al-Qur'an in general is the general benefit of mathal is that it can visualize things that are abstract.